Pendampingan Tahsinul Qur’an di Pondok Pesantren Darur- Rohman Blu’uran Sampang - Wasik, Wasik; Muqoffi, Muqoffi; Zainuddin, Zainuddin (Al-Khidmah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This research explores the Tahsinul Qur'an Mentoring program implemented at the Darur-Rohman Islamic Boarding School, an activity that is generally used to facilitate students in understanding and reading the Al-Qur'an. This research aims to evaluate Tahsinul Qur'an assistance in improving students' competence in reading the Qur'an. This research uses a qualitative approach which includes interviews, observations and document analysis to collect data from students at the Miftahul Ulum Darur-Rohman Islamic Boarding School. The research results revealed that Tahsinul Qur'an assistance had a positive impact in strengthening students' skills in reading the Koran. Santri involved in this program experienced significant improvements in understanding and pronunciation of reading the Al-Qur'an. In addition, this research identified key factors that contributed to the success of Tahsinul Qur'an assistance including the role of experienced teachers, and a learning environment that support. Recommendations are given to expand Tahsinul Qur'an assistance in Islamic boarding schools as an effort to enrich students' understanding and skills in reading the Qur'an